Advanced Research on Animal Venoms in China - Lai, Ren; Lu, Qiumin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Recently, Chinese researchers have made significant progress in animal venom research in comprehending the diversity and complexity of these molecules and their potential applications in medicine, biotechnology, and as research tools. Advancements in 'omics' technologies such as proteomics, genomics, and transcriptomics have empowered Chinese researchers to identify and analyze venom-coded genes and proteins, revealing a kaleidoscope of novel peptide toxins with diverse functions and activities. The reprint focus on the perspective on some of the most recent and dynamic contributions of animal toxins research by Chinese researchers. The purpose of this reprint is to provide the latest work by Chinese researchers on the discovery of animal toxins, the mechanism underlining their actions, the mining of drug leads from peptide toxins, and the diagnosis and treatment of bites or stings by venomous animals.